(3GdaUjMs - (3GdTjHGfqj, CHh GdYHGS, KYdH, CMeO Hf jMji Hf RjO Hf SjGQ, (B291 (3g`s ((3eMeO MSjf GdbRhjfjs)
(3ChdgG (B:s
(3gPG cJGH GNJjGQ aUjM GdcdGe eeG jLQj aj cdGe GdfGS(B...s
(3BNQgG (B:s
(3hGdYGeI Jbhd(B: (3NeSI ChQGb, hGdUhGH(B: (3hQbGJ(B. (3hJchf GdChQGb LeY GdhQb ef GdeUMa hGdfHGJ hcd TjA(B.s
(3jdjg cJGH(B: (3JeGe GdaUjM, ef (B47 (3MJi fgGjI GdeNWhWIs
(3JHUQI GdYfhGf (B:s
(3GdaUjM aj GddZIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B323s
(3GdCYdGe(B: (3L(B1(3, U(B267s
Keywords: (3GddZIs